Pharmacokinetics and Bioavailability of Carprofen in Rainbow Trout (Oncorhynchus mykiss) Broodstock - Uney, Kamil; Durna Corum, Duygu; Terzi, Ertugrul; Corum, Orhan (MDPI AG, 2021)
The aim of this study was to determine the pharmacokinetics of carprofen following intravenous (IV), intramuscular (IM) and oral routes to rainbow trout (Oncorhynchus mykiss) broodstock at temperatures of 10 ± 1.5 °C. In this study, thirty-six healthy rainbow trout broodstock (body weight, 1.45 ± 0.30 kg) were used. The plasma concentrations of carprofen were determined using high-performance liquid chromatography and pharmacokinetic parameters were calculated using non-compartmental analysis. Carprofen was measured up to 192 h for IV route and 240 h for IM, and oral routes in plasma. The elimination half-life (t1/2λz) was 30.66, 46.11, and 41.08 h for IV, IM and oral routes, respectively. Carprofen for the IV route showed the total clearance of 0.02 L/h/kg and volume of distribution at steady state of 0.60 L/kg. For IM and oral routes, the peak plasma concentration (Cmax) was 3.96 and 2.52 μg/mL with the time to reach Cmax of 2 and 4 h, respectively. The bioavailability was 121.89% for IM route and 78.66% for oral route. The favorable pharmacokinetic properties such as the good bioavailability and long t1/2λz for IM and oral route of carprofen suggest the possibility of its effective use for the treatment of various conditions in broodstock.
Keywords: RS1-441; carprofen; Pharmacy and materia medica; broodstock; bioavailability; pharmacokinetics; rainbow trout; Article; 3. Good health